Chromatin structure and gene transcription of recombinant p53 adenovirus vector within host - Ning, Duo; Deng, Yuqing; Tian, Simon Zhongyuan (Frontiers in Molecular Biosciences, 2025)
IntroductionThe recombinant human p53 adenovirus (Ad-p53) offers a promising approach for cancer therapy, yet its chromatin structure and effects on host chromatin organization and gene expression are not fully understood.MethodsIn this study, we employed in situ ChIA-PET to investigate the colorectal cancer cell line HCT116 with p53 knockout, comparing them to cells infected with the adenovirus-vector expressing p53. We examined alterations in chromatin interactions and gene expression following treatment with the anti-cancer drug 5-fluorouracil (5-FU).ResultsOur results indicate that Ad-p53 forms a specific chromatin architecture within the vector and mainly interacts with repressive or inactive regions of host chromatin, without significantly affecting the expression of associated genes. Additionally, Ad-p53 does not affect topologically associating domains (TADs) or A/B compartments in the host genome.DiscussionThese findings suggest that while Ad-p53 boosts p53 expression, enhancing drug sensitivity without substantially altering host HCT116 chromatin architecture.